Chemistry and Biology Terminology and Modern Methods of its Teaching - Abdullayeva Albina Ergashevna (Genius Journals, 2022)
This article analyzes the terminology of natural sciences for students majoring in armachetics and biology, chemistry, which is currently emerging in each field due to the demand for foreign languages in their field, and offers suggestions for problems in teaching.
Keywords: Absolute zero; actual yield; chemistry; biology